Dynamic Relationship between the Stock Market and the Macroeconomic Factors: Preliminary Evidence from Nepalese Stock Market - Bhattarai, Rama Chandra; Joshi, Navan Krishna (Economic Journal of Nepal, 2011)
This paper examines the dynamic relationship between the stock market and macroeconomic factors represented by inflation, money supply and interest rate for a stock market of a single small developing country such as Nepal. Using Johansen and Juselius (1990) method of multivariate cointegration for the period of July 1995 to June 2006. the study documented both short run and long run interdependence between stock index and some macroeconomic variables. Regarding stock index and consumer price index the multivariate results suggested long run relationship and positive and unidirectional (short run) relationship from consumer price index to stock index. The multivariate results uncovered long run relationship between stock index and Treasury bill rate but no short run linkages. The variance decompositions results showed a strong relative exogeneity of stock while the impulse response graphs showed that the response of stock index to shocks in macroeconomic variables did not persist for long period. Key words: Stock market; Money supply; Interest rate; Nepal Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.4, October-December, Issue No. 120, 2007 Page: 215-231 Uploaded date: 22 July, 2011